Анализ результатов лазерной коррекции миопической рефракции с использованием технологии ReLEx SMILE - Завгородняя, Н. Г.; Поплавская, И. А.; Михальчик, С. В.; Zavgorodnya, N. G.; Poplavska, I. O.; Myhalchyk, S. V.; Завгородня, Наталія Григорівна; Поплавська, Ірина Олександрівна; Михальчик, Сергій Валерійович (Белорусская медицинская академия последипломного образования, 2020)
Актуальность и цель. В настоящее время все большую популярность завоевывает новая методика ReLEx SMILE, которая позиционируется как операция, не требующая значительных ограничений в период реабилитации, однако, результаты данного вида вмешательств недостаточно изучены. Проанализировать результаты лазерной коррекции ReLEx SMILE у пациентов с миопией и сложным миопическим астигматизмом. The results of laser vision correction using ReLEx SMILE technology in 124 patients (248 eyes) were analyzed. 71 eyes (28,6 %) showed mild myopia, 163 eyes (65,7 %) - moderate myopia, and others - high myopia (5,6 %). On the first day after the laser correction ReLEx SMILE, the expected visual acuity was noted in 229 eyes (92,3 %), the autokeratorefractometry indexes had fluctuations from + 0.5 to -0.5d. Full adaptation of the corneal incision and epithelialization in the access area was evident. As a result, a month later, the maximum corrected visual acuity was achieved in 97,2 %, and autokeratorefractometry indicators were from +0.25 to -0.25 d, which allows to recommend this type of vision correction as a method of choice in patients with myopic refraction.
Analysis of the results laser correction of myopic refraction using ReLEx SMILE technology